GOOSE Message to Protect and Control Applications Using WLAN With IEC 61850v - Elhadi Emhemed Aker; Mohamed Milood Almelian; N. H. Ali (Surman Journal of Science and Technology, 2024)
The new IEC 61850 integrates stability, security, interoperability, modeling, mapping to a substation, and reliability. Presently, at the time being expensive fiber-based Ethernet LAN is the most prevalent technology for medium and low-voltage distribution substations. To overcome this problem Wireless Local Area Network (WLAN) has been introduced for its suitability and applications that are compliant with IEC 61850: automation, metering; control, monitoring; and over-current protection. In this paper, the IEEE 802.11n WLAN is studied when used in various IEC 61850-supported applications for substation automation. GOOSE message is a very important application to protect and control applications using the new protocol IEC 61850.